MOTIVATION AND AFFECTIVE PRINCIPLE IN LANGUAGE LEARNING: IMPLICATIONS TO EFL LEARNERS AND TEACHERS - Tobias Gunas (Unika Santu Paulus Ruteng, 2016)
Teaching and learning language are essentially interrelated with the factor of motivation and affective principle. Many researches have revealed that motivation factor and affective principle have contributed to the success of language learning. In this case, the effect of motivation and affective principle prove to be of importance for learners in the course of language learning. This article is mainly intended to explore the concept of motivation, affective principle, types of motivation, and motivational strategies as well as implications.